Anak Angkat dan Kedudukannya Terhadap Harta Peninggalan Orangtua Angkat Menurut Hukum Perdata di Indonesia - Suryaatmadja, Liliana; Sarjana, I Made (Ethics and Law Journal: Business and Notary, 2024)
Children are God's gifts for which all parents should be grateful, to be raised and cared for properly is the duty of parents as they should be. Regardless of blood relationship or not, adopted and biological children both have gifts that are just as beautiful in the eyes of their parents. Adopted child himself, has a definition in which his rights are transferred from the scope of power of parents, or legal guardians before the law, or other people who have full responsibility for the child's rights including education, care, providing for and raising into the family environment of his adoptive parents based on a legal decision . The purpose of making this journal is of course to find out the position of adopted children in relation to the assets of their foster parents. So that the position of the adopted child is one of the most important in the right to inherit the inheritance of his parents. Through the Judicial-Normative research method, the author himself reviews the laws and regulations and is equipped with literature related to the language. The culmination of the results of this study, where the position of adopted children has no rights as heirs to the inheritance of their adoptive parents according to the perspective of Civil Law. To guarantee the legal status of adopted children, a court decision is required when someone adopts a child. Abstrak Anak merupakan anugerah Tuhan yang patut di syukuri oleh semua orangtua, dibesarkan dan dirawat dengan baik merupakan tugas orangtua sebagaimana mestinya. Terlepas dari hubungan darah atau tidak, anak angkat dan anak kandung sama-sama memiliki anugerah yang sama indahnya dimata orangtua. Anak angkat sendiri, memiliki deifinisi dimana haknya dipindah tangankan dari lingkup kekuasaaan orangtua, ataupun wali yang sah dimata hukum, atau oranglain yang memiliki tanggung jawab penuh atas hak anak tersebut diantaranya pendidikan, perawatan, menafkahi dan membesarkan ke dalam lingkungan keluarga orangtua angkatnya berdasarkan keputusuan hukum. Tujuan dari pembuatan jurnal ini tentu untuk mengetahui kedudukan anak angkat terhadap harta orangtua asuhnya. Sehingga kedudukan sang anak angkat merupakan salah satu yang penting dalam hak mewarisi harta peninggalan orangtuanya. Melalui metode penelitian Yudiris-Normatif, penulis sendiri mengkaji dengan peraturan perundang-undangan dan dilengkapi dengan bahan literature yang berkaitan dengan bahsan. Yang menjadi puncak dari hasil penelitian ini, dimana kedudukan anak angkat tidak memiliki hak sebagai ahli waris harta peninggalan orangtua angkatnya menurut kacamata Hukum Perdata. Untuk menjamin status hukum anak angkat, diperlukan putusan pengadilan ketika seseorang mengangkat anak. Kata Kunci : Kedudukan anak angkat, Akta Notaris, Akta Penyerahan Anak.